2008
DOI: 10.2134/agronj2007.0373
|View full text |Cite
|
Sign up to set email alerts
|

A Wheat Grazing Model for Simulating Grain and Beef Production: Part II—Model Validation

Abstract: Computer models must be thoroughly evaluated before being used for decision-making. Th e objective of this paper is to evaluate the ability of a newly developed wheat grazing model to predict fall-winter forage and winter wheat (Triticum aestivum L.) grain yield as well as daily weight gains of steer (Bos taurus) grazing on wheat pasture in Oklahoma. Experimental data of three independent fi eld studies were used. Th e fi rst was a variety trial in which fall-winter forage and grain yields were harvested. Th e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The five crop coefficients were previously calibrated for the cultivar Jagger using wheat data measured at the USDA‐ARS Grazinglands Research Laboratory in central Oklahoma during 2004 to 2006 (Zhang et al, 2008a). The calibrated crop coefficients of P1V, P1D, P5, G1, G2, G3, and PHINT for Jagger were 40, 63, 450, 17, 25, 1.5, and 90, respectively [P1V: days at optimum vernalizing temperature required to complete vernalization; P1D: percentage reduction in development rate in a photoperiod 10 h shorter than the optimum relative to that at the optimum; P5: grain‐filling phase duration (°C× d); G1: kernel number per gram canopy weight at anthesis; G2: standard kernel size under optimum conditions (mg kernel −1 ); G3: standard, nonstressed dry weight of a single tiller at maturity (g tiller −1 ); PHINT: interval between successive leaf tip appearance (°C× d)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five crop coefficients were previously calibrated for the cultivar Jagger using wheat data measured at the USDA‐ARS Grazinglands Research Laboratory in central Oklahoma during 2004 to 2006 (Zhang et al, 2008a). The calibrated crop coefficients of P1V, P1D, P5, G1, G2, G3, and PHINT for Jagger were 40, 63, 450, 17, 25, 1.5, and 90, respectively [P1V: days at optimum vernalizing temperature required to complete vernalization; P1D: percentage reduction in development rate in a photoperiod 10 h shorter than the optimum relative to that at the optimum; P5: grain‐filling phase duration (°C× d); G1: kernel number per gram canopy weight at anthesis; G2: standard kernel size under optimum conditions (mg kernel −1 ); G3: standard, nonstressed dry weight of a single tiller at maturity (g tiller −1 ); PHINT: interval between successive leaf tip appearance (°C× d)].…”
Section: Methodsmentioning
confidence: 99%
“…The wheat grazing model simulated wheat and cattle growth interactively and dynamically (in a daily time step), and thus was capable of simulating the tradeoffs between livestock and grain production. Zhang et al (2008a) evaluated the wheat grazing model at three locations in central Oklahoma, and reported that when the model was well calibrated, it was capable of predicting aboveground biomass, grain yield, and cattle live weight gain (LWG) for various climate and soil conditions. Using the grazing model, Mauget et al (2009) evaluated the value of El Nino‐Southern Oscillation forecast information for managing dual‐purpose wheat in the southern Great Plains by varying planting dates, N rates, and stocking density.…”
mentioning
confidence: 99%
“…Many researchers throughout the world tested and evaluated the ability of the CERES-Wheat model to simulate top dry biomass and grain yield, and reported satisfactory results (e.g., IAEA-TEC-DOC, 2000; Bannayan et al, 2003;Panda et al, 2003;Rinaldi, 2004). Zhang et al (2008a) evaluated the wheat grazing model at three locations in central Oklahoma, and reported that the model, if well calibrated, has the potential to predict top biomass and grain yields under various climate and soil conditions.…”
Section: Wheat Grazing Modelmentioning
confidence: 99%
“…Th e fi ve crop coeffi cients were previously calibrated for the variety Jagger using wheat data measured in central Oklahoma during (Zhang et al, 2008a. Jagger was the dominant cultivar widely grown in Oklahoma in the past several years (http://www.nass.usda.gov/).…”
Section: Crop Coeffi Cientmentioning
confidence: 99%
“…4.02) for simulating production of wheat grain and stocker cattle grazing on wheat during late fall and early spring for the U.S. Southern Great Plains. Evaluation and validation of the new model are critical to its acceptance and adoption by potential users and are presented in a companion paper in this issue (Zhang et al, 2008).…”
mentioning
confidence: 99%